1999
DOI: 10.1002/(sici)1520-7560(199909/10)15:5<314::aid-dmrr56>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of free insulin-like growth factors in obese subjects: the impact of Type 2 diabetes

Abstract: Background Obese subjects show major abnormalities in the growth hormone (GH)/insulin‐like growth factor (IGF) system. Furthermore, they are prone to develop Type 2 diabetes, but the impact of diabetes plus obesity on the GH/IGF system remains unknown. Methods We compared overnight fasting serum levels of free and total (extractable) IGF‐I and ‐II, IGF‐binding protein (IGFBP) ‐1, ‐2 and ‐3, and the high affinity GH‐binding protein (GHBP) in matched groups of lean subjects (n=26) and obese subjects without (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
156
4
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(178 citation statements)
references
References 44 publications
17
156
4
1
Order By: Relevance
“…In obese subjects without T2DM, IGFBP-2 levels were reduced and became further reduced in those patients that also had T2DM. As a point of interest, in T1DM subjects, IGFBP-2 was actually increased [57], as also reported by others in T1DM [58] and diabetic retinopathy [59], suggesting that T1DM and T2DM each have a unique impact on IGFBP-2 levels, perhaps related to differences in insulin sensitivity. Low circulating levels of IGFBP-2 have also been reported in lifestyle-related childhood obesity (with normal growth in spite of reduced GH secretion) and pre-pubertal obese subjects [60].…”
Section: Metabolic Effects Of Igfbp-2supporting
confidence: 75%
See 1 more Smart Citation
“…In obese subjects without T2DM, IGFBP-2 levels were reduced and became further reduced in those patients that also had T2DM. As a point of interest, in T1DM subjects, IGFBP-2 was actually increased [57], as also reported by others in T1DM [58] and diabetic retinopathy [59], suggesting that T1DM and T2DM each have a unique impact on IGFBP-2 levels, perhaps related to differences in insulin sensitivity. Low circulating levels of IGFBP-2 have also been reported in lifestyle-related childhood obesity (with normal growth in spite of reduced GH secretion) and pre-pubertal obese subjects [60].…”
Section: Metabolic Effects Of Igfbp-2supporting
confidence: 75%
“…abnormal low IGFBP-2 leading to abnormal elevated free IGF-I) and in turn, IGFBP-2 contribution to maintenance of metabolic functions. A study by Frystyk et al [57], investigated potential alterations in the GH/IGF axis following overnight fasting in matched groups of lean subjects, obese subjects with or without T2DM, and subjects with T1DM. In obese subjects without T2DM, IGFBP-2 levels were reduced and became further reduced in those patients that also had T2DM.…”
Section: Metabolic Effects Of Igfbp-2mentioning
confidence: 99%
“…There are few studies that have examined IGF-I levels in type II diabetes, but recent prospective epidemiologic studies suggest that higher IGF-I levels may actually lower diabetes risk [48,49]. One study that compared obese diabetics, obese non-diabetics, and lean controls, found that serum IGF-I were elevated among obese women with and without type II diabetes, although only the difference between non-diabetics and controls achieved statistical significance [50]. It is interesting to note that obesity increases risk of diabetes and post-menopausal breast cancer, but is inversely associated with density and pre-menopausal breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, high levels of GHBP are associated with hyperinsulinaemia and obesity, with GHBP falling significantly in the obese after weight loss, with normalization of insulin levels [84,85]. GHBP levels correlate significantly with fat mass, and because adipocytes express GHRs, it is possible that elevated GHBP levels simply reflect an increase in fat mass [84].…”
Section: Insulin Effect On Gh Receptor Expressionmentioning
confidence: 99%